Blueprint : Pzg Spare Part Enterprise “Magic Pocket” / Muhammad Hafizzullah Juha Seman - Juha Seman, Muhammad Hafizzullah (2020)
The PZG Spare Part Enterprise is a new company that will be operated in Malaysia. The name of this company is come out from one of the idols in motorsport. This business consists of four partners that motivate to be a successful entrepreneur. The members are including general manager, Operations manager, marketing manager and financial manager. Our business is located at Tumpat, Kelantan. After doing some research on the business opportunity that available at Tumpat, we have decided to specify our business in selling our product. Our business will introduce a new product namely Magic Pocket which is a product that creates for those who love to ride especially a long-distance riding. As the entrepreneur that understand what are the consumers’ need, this company take the problems seriously in order to solve the problems with technology. As today, technology plays an important role in this era. Low income users, youngster riders and the entrepreneur that related to the vehicle accessories will be our target market. Also, in the future, we will expand our target market to foreign country and we believe that they will be interested in our product